SISTEM MODUL MIKROFILTRASI DALAM PEMURNIAN L-THEANINE DARI TEH HIJAU LOKAL (Camellia assamica) Pekoe UNTUK MINUMAN FUNGSIONAL - Agustine Susilowati; Aspiyanto Aspiyanto; Hakiki Melanie; Yati Maryati (Prosiding SNST Fakultas Teknik, 2010)
Microfiltration (MF) module system had a potential use in purifying of L-Theanine of local green tea (Camellia assamica) grade Pekoe for functional drink as anti stress compound. Purification process was performed through MF membrane of 0.2 µm at pump motor frequency of 20 Hz, room temperature, and operation pressure of 4 and 6 bar for 30, 60, 90, 120, 150, 180, 210, 240, 270 and 300 minutes. The experiment result showed that MF system was able to pass more much L-Theanine in permeate, but retained more much dry matter and dissolved protein in retentate. Long purification time would decrease permeate flux value and L-Theanine concentration in permeate, but increased dry matter and dissolved protein in retentate. Optimum operation condition based on the highest concentration of L-Theanine in permeate at operation pressures of 4 and 6 bar for 120 and 240 minutes was able to pass L-Theanine in permeate of 86.33 % and 71.21 from all L-Theanine prior to process. Permeate as source of L-Theanine at optimum condition gave permeate flux values of 13.72 and 15.55 L/m2.hour with concentrations of L-Theanine of 10.721 % and 10.203 % (dry weight), dissolved protein of 2.1 and 1.8 mg/mL, and   dry matter of 1.342 and 1.712 %. Retentate has a potential use as functional compounds for anti oxidant,  anti cancer, anti diabetes and anti cholesterol. Key Words : Camellia  asssamica, L-Theanine, Microfiltration (MF), permeate, retentate.